A review of the water resources of Ghana in a changing climate and anthropogenic stresses - Agodzo, Sampson K.; Bessah, Enoch; Nyatuame, Mexoese (Frontiers in Water, 2023)
An extensive narrative review approach is adopted to present existing information on the consumptive and non-consumptive uses and their related issues, such as floods and droughts, climate and the environment in Ghana. Total annual rainfall in the country ranges between 800 mm/y (south-east coat) and 2,000 mm/y (south-west coast) with a bimodal and mono-modal patterns in the south and north, respectively. Annual total runoff from the 3 river systems (the Volta river system, the South-western river system and the Coastal river system) in Ghana is estimated at 40 billion m3 out of about 53 billion renewable freshwater resources. Groundwater yields ranges from 6 m3/h in the Volta basin sedimentary formations to 180 m3/h in the limestone formations. It is estimated that the total water withdrawal as a percentage of total renewable water resources is about 2%. At an average per capita consumption of water of 50 l/p/d, estimated daily water demand for the 2021 population of 31 million people stands at about 566 million m3/y. Current water supply systems are overstretched and it is further estimated that about US 240 million is required per year as capital expenditure in urban and rural water supply. Moreover, climate change is projected to increase the scarcity of water in future. Wastewater generated through domestic and industrial uses including storm water in urban Ghana is estimated at about 760 million m3/y. Ghana's irrigation potential to reduce climate change impact on agriculture is put at between 0.36 and 2.9 million ha, accounting for about 66.4% of the consumptive water withdrawal. Estimated water demand for cattle, sheep and goats in 2010 was put at about 22 million m3/y. Other services obtained from surface water are the provision of fish (the Volta Lake is estimated to contributes to 16% of total catch in Ghana); hydropower generation accounting for about 40% of total power installed capacity (Akosombo = 1,020 MW, Kpong = 160 MW, and Bui = 404 MW); water transportation (notably on the Volta Lake); tourist attractions [are 550 km Ghana's shoreline that has about 90 lagoons, the Volta Lake, the lower Volta (e.g., Sogakope, Ada) and some other inland waters like Lake Bosumtwi] and wetlands (recognized by RAMSAR convention of 1971) In the legal context, water governance issues are handled by various institutions created by Acts of Parliament.